Country‐level correlates of the Dark Triad traits in 49 countries. Issue 6 (1st July 2020) - Jonason, Peter K.; Żemojtel‐Piotrowska, Magdalena; Piotrowski, Jarosław; Sedikides, Constantine; Campbell, W. Keith; Gebauer, Jochen E.; Maltby, John; Adamovic, Mladen; Adams, Byron G.; Kadiyono, Anissa Lestari; Atitsogbe, Kokou A.; Bundhoo, Harshalini Y.; et al.
Abstract: Objectives: The Dark Triad traits (i.e., narcissism, psychopathy, Machiavellianism) capture individual differences in aversive personality to complement work on other taxonomies, such as the Big Five traits. However, the literature on the Dark Triad traits relies mostly on samples from English‐speaking (i.e., Westernized) countries. We broadened the scope of this literature by sampling from a wider array of countries. Method: We drew on data from 49 countries ( N  = 11, 723; 65.8% female; AgeMean  = 21.53) to examine how an extensive net of country‐level variables in economic status (e.g., Human Development Index), social relations (e.g., gender equality), political orientations (e.g., democracy), and cultural values (e.g., embeddedness) relate to country‐level rates of the Dark Triad traits, as well as variance in the magnitude of sex differences in them. Results: Narcissism was especially sensitive to country‐level variables. Countries with more embedded and hierarchical cultural systems were more narcissistic. Also, sex differences in narcissism were larger in more developed societies: Women were less likely to be narcissistic in developed (vs. less developed) countries. Conclusions: We discuss the results based on evolutionary and social role models of personality and sex differences. That higher country‐level narcissism was more common in less developed countries, whereas sex differences in narcissism were larger in more developed countries, is more consistent with evolutionary than social role models.